Enhancement of Red Upconversion Emission of ZnS: Er3+/Yb3+ Powders Synthesized via Solid Phase Reaction Method by Introducing Metal Fluoride. Issue 8 (28th February 2022) - Dong, Yanhao; Yang, Qinghua; Wang, Huanping; Li, Yinqun; Xu, Shiqing
Abstract: ZnS: Er 3+ /Yb 3+ powders were synthesized by a common solid phase reaction method with NaF, CaF2, LiF, AlF3 and MgF2 as dopant. The enhancement mechanisms of different metal fluorides (NaF, CaF2, LiF, AlF3 and MgF2 ) and concentrations (0 wt% ∼9 wt %) on structure, morphology and optical properties of ZnS: Er 3+ /Yb 3+ powders were investigated systematically. The results revealed that as synthesized ZnS: Er 3+ /Yb 3+ powders are main exhibited as wurtzite phase, the lattice constant, unit cell volume and lattice strain increase with metal fluoride codoping, which indicates the increase of resultant distortion. As synthesized ZnS: Er 3+ /Yb 3+ powders have an intense red upconversion emission centered at 663 nm and a weak green upconversion emission centered at 567 nm under the excitation of a 980 nm laser diode. Compared with ZnS: Er 3+ /Yb 3+ powders synthesized without metal fluoride, the upconversion emission intensities of ZnS: Er 3+ /Yb 3+ powders synthesized with LiF, NaF, MgF2, AlF3 and CaF enhance ∼12 times, ∼9 times, ∼5 times, ∼3 times and ∼3 times, respectively. The strong red upconversion properties make the ZnS: Er 3+ /Yb 3+ powders synthesized with metal fluoride a potential application in the field of light emitting diodes. Abstract :